APPLYING MONTESSORI METHOD TO IMPROVE EARLY CHILDHOOD ENGLISH SKILL - Nurul Azizah Ria Kusrini; Eka Rizki Amalia; Salis Khoiriyati (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
The Montessori method has been gaining more attention in the last five years. Some preschools and kindergarten have been applying the Montessori method in the English learning activity. However, the method is mostly applied by prestigious schools based on several factors: the school’s readability related to the budget, the stakeholders and teachers as well as the parents’ perceptions, the teacher’s competency, etc. This case study is intended to investigate the implementation of English teaching and learning by using the Montessori method in preschool and kindergarten settings. Six teachers participated in the study. The data were collected from interviews and observations. The results indicate that applying the Montessori method in English learning activities can result positively in students' English ability and performance. The findings propose several suggestions related to the issue of English for early childhood education.